Measurement of magnetic susceptibility of Rajmahal traps - MAHASETH, R. N.; DUTTA, S. K. (MAUSAM, 1983)
Necessary apparatus for the measurement or magnetic susceptibility was built up The average magnetic suceptibility or the Rajmahal traps in eastern India is estimated to be 0.554 x 10-3 emu/ce and is thus low compared to basalt from over areas of the world such. as Japan and Great Britain. Heating effect on magnetic susceptibility has been studied. Generally the susceptibility Increases with the increase or temperature.